(untitled) (Discourse of Law and Administration, 2022)
At the time of the entry into force of the Code of Civil Procedure, the legislator did not provide for the possibility of appealing against the decision of the court of second instance with a complaint. The first changes in this respect took place in 1996 in connection with the introduction of the third instance – a cassation appeal heard by the Supreme Court. Subsequent changes were related to the right to the party to be heard in the instance proceedings and concerned the appeal against the judgments of the second-instance court to a different composition of the court in the case in which the second-instance court ruled for the first time. The study discusses the concept of challenge and judicial remedies in the context of the jurisprudence of the Constitutional Tribunal. The paper presents the evolution of changes in the scope of appealing against the decision of the second instance court and the reasons for these changes. A critical analysis of the current legal status, which is in force in the Code of Civil Procedure as of November 7, 2019, was performed. The last part was devoted to the de lege ferenda proposal.